Ecotourism Development in the Tanjung Papuma Area, Jember Regency to Attract Generation Zs Visiting Interest - Susilo, Anugerah Aji; Satrya, I Dewa Gde (AIBPM Publisher, 2022)
Tanjung Papuma is a beach that has become a tourist spot in Jember Regency, East Java, Indonesia. Tanjung Papuma is located in a protected forest area managed by Perhutani. This forest is still natural in which it is a habitat for various flora and fauna such as deer, partridges, to Javanese langurs. Considering the Tanjung Papuma area which is a protected forest, it is necessary to develop ecotourism-based tourism. The ecotourism development that has been carried out will be linked to attracting visiting interest for Generation Z. Generation Z was chosen as the research subject because sustainable tourism behavior is increasingly being recognized as a popular topic among young tourists. The research method used is qualitative with the type of case study research. In extracting data, it is done through observation and interview methods. Interviews were conducted directly by researchers with key informants from tourism object managers, residents, and generation Z. The results showed management of the Tanjung Papuma has carried out tourism development by paying attention to ecotourism principles. However, some aspects are not optimal and need to be improved.